Assessment Practices of Integrated Curriculum in Morang: A Case Study of Private School - Khatri, Rajesh (Academia Journal of Research and Innovation, 2026)
Assessment practices in early-grade education play a critical role in supporting children's holistic development through integrated curricula which implement learner-centered educational methods. In Nepal the Integrated Curriculum (IC) for Grades 1-3 implements a new approach which focuses on interdisciplinary learning and child-centered teaching methods while assessment is designed to serve as an ongoing assessment tool which helps learners to progress. However, limited empirical attention has been given to how these assessment principles are enacted in classroom practice especially in private school contexts. This study examines the assessment practices of the Integrated Curriculum (Grades 1-3) in a private school in Morang District Nepal. The study explores how school leaders and teachers apply assessment principles through their educational practices to help children achieve their complete development. The research focuses on classroom observation which includes ongoing monitoring and portfolio management and rubric implementation and authentic learning activities that expose students to real-world situations. The researchers employed a qualitative case study design which used an interpretive framework to study actual classroom environments. The researchers selected the principal and teachers as main study participants while they collected data through classroom observations and interviews and assessments of students' workbooks and assessment records. The research method provided a complete comprehension of assessment methods which were planned and assessment methods which were actually used in educational settings. The research results show that there exists a discrepancy between the authentic assessment standards which the integrated curriculum promotes and the authentic assessment standards which teachers apply in their classrooms. The leadership team understands the concept at a basic level but they apply it inconsistently because exam-based methods and low parental participation continue to shape their assessment methods. The school has not reached complete implementation of authentic assessment practices yet.